The Effect of Husband’s Support on Fear of Cancer Recurrence in Gynecological and Breast Cancer Survivors - Heryani, Heryani; Afiyanti, Yati; Azidin, Yustan; M. Syafwani; Solikin, Solikin; Rahmayani, Dini (STIKES Suaka Insan, 2025)
Cancer is a leading cause of death, and survivors face a wide range of therapies and psychological challenges. A key need reported by cancer survivors, particularly gynecological and breast cancer survivors, at the end of their treatment is fear of recurrence, which many factors, including husband support, can influence. The purpose of this study was to analyze the effect of husband support on fear of recurrence in gynecological and breast cancer survivors. This study was conducted at Ulin Hospital, Banjarmasin, with 211 respondents who underwent outpatient evaluation and had undergone at least one treatment. The research instrument used the Fear of Cancer Recurrence Inventory (FCRI) questionnaire. This study design was cross-sectional. The main findings of this study showed no statistically significant association between husband support and fear of recurrence in gynecological and breast cancer survivors (P-value 0.06). Based on the statistical results, the global score is not significant, but the specific domains show significance there was a specific correlation in one subtype of husband's support (instrumental support, specifically in the contributing factor domain, with a p-value of 0.03 and a correlation coefficient of r=?0.15) with one domain of fear. The conclusion of this study indicates that overall, there is no relationship between husband's support and the contributing factor, but there is a significant relationship between instrumental and important support. This can provide recommendations for further research, including using a longitudinal design to obtain more accurate results.